Randai Training Strategy in Padang Pariaman - Rembulan Catra Banyu Biru; Jamaris Jamaris (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is motivated by the activity of the randai trainees in Korong Kasai, who are generally teenagers who are in Korong Kasai, this is presumably because the trainer uses a suitable strategy. Apart from that, there are also some uniqueness in the randai training in Korong Kasai, which is a place or stage for randai training that is designed as attractive as possible so that participants are enthusiastic in randai training, there are taught ulu ambek which are martial arts for randai participants, and required deta use training takes place. This study aims to describe how the randai training strategy used by the smart trainer in Korong Kasai Nagari Tapakis, Padang Pariaman Regency. Components of training strategies, namely the material used and taught, the media used, and evaluations used. This type of research uses a qualitative descriptive approach. Data collection techniques used, namely observation, interviews, and documentation. Data analysis uses qualitative data analysis, namely data reduction, data presentation, and conclusion. The author's findings, namely training material in the form of smart movements that do not have the name of the movement and coupled with martial arts known as ulu ambek, use practical methods and auditive media (relying on sound abilities), and evaluation is done by the coach instructing participants to repeat re-randai after the randai training is complete.Keywords: Training Strategy, Randai, Ulu ambek